KOMPARASI KESEJAHTERAAN NELAYAN PAYANG DI DESA SUNGAI PISANG KECAMATAN BUNGUS TELUK KABUNG DENGAN DESA AMPANG PULAI KECAMATAN XI KOTO TARUSAN - Gunadi Ilham; Paus Iskarni (JURUSAN GEOGRAFI FIS UNP, 2020)
ABSTRACT T ABSTRACT This research aims to discuss about the walfare comparison of fisherman payang in the village Sungai Pisang sub-districts Bungus Teluk Kabung with village Ampang Pulai sub-districts XI Koto Tarusan. Metods are used in a descriptive method with a quantitative approach. Variables in this study are income, food, clothing, boards, education and health. The sample determination in the study was done using simple random sampling (metode acak sederhana). The data collection techniques used are poll techniques. The result of the research is being posted in the village Sungai Pisang with the village of Ampang Pulai by Badan Koordinasi Keluarga Berencana Nasional (BKKBN 2014), obtained by Sungai Pisng village from 61 fisherman 40 people (65,57) Keluarga Sejahtera II and 21fisherman village Ampang Pulai, 18 people (85,71) Keluarga Sejahtera II. Keyword : Fisherman, Walfare, Comparison